The Exception of National Treatment Principle of Gatt in Indonesia - Yokhebed Arumdika Probosambodo (Journal of Law and Policy Transformation, 2018)
The purpose of this study is to describe clearly and carefully about the exception of National Treatment principle of the GATT/WTO whether it is justifiable or not. It also aims to analyze the obstacles that hinder Indonesia in implementing international agreements, in particular the National Treatment principle of GATT/WTO completely, and to find out the consequences if Indonesia continues to apply the exceptions of the National Treatment principle of GATT/WTO. Based on the result of this research showed that the exceptions of the National Treatment principle that was imposed by Indonesia was violating the rule of GATT/WTO. Furthermore, the uncertain regulation and the confusion are the obstacles that hinder Indonesia in implementing the National Treatment principle of GATT/WTO completely, thus Indonesia should make a clearly decision whether it is a Monism or a Dualism country to determine which law should be more supreme, International Law or National Law?. The consequences impose on a state when violating a GATT/WTO agreement is very influential and harms the state itself, because it would be excommunicated from the international trade.